Penanaman Nilai Agama dan Moral Melalui Metode Cerita Bergambar pada Anak Usia 4-5 Tahun di Kober Sriwijaya Sadar Sriwijaya - Munayah, Munayah (Institut Agama Islam Sunan Giri Ponorogo, 2024)
This research aims to determine teachers' strategies in instilling religious and moral values ​​in children at the Sriwijaya Sadar Sriwijaya KB using the singing method. This research uses a qualitative descriptive research type. Qualitative descriptive research is a research model that is oriented towards natural phenomena or symptoms and this form of research includes Classroom Action Research (CAR). The subjects of this research were students from the Sriwijaya KB School aged 4-5 years in Class B, totaling 15 children. In this case, it is positioned as a research subject because children aged 4-5 years are considered to have not developed their moral values ​​well according to the following criteria: the child is not yet accustomed to saying hello, the child cannot speak politely to friends, the child cannot memorize short letters. The results of the research show that the singing method used by children at Baitul Ilmi PAUD in learning activities is improving. Recognizing letters and numbers is improving, so that children don't get bored easily following lessons, don't chat alone, remember and memorize quickly and teachers can make the singing method an alternative model or strategy in learning. It can be concluded that the singing method used by teaching assistance students, as an introduction to letters and numbers in children aged 4-5 years, is more improved than before and the achievement of quality learning in accordance with achievement standards is also achieved well.